Inheritance of Downy Mildew Resistance In Pearl Millet (PENNISETUM Glaucum (B.) BR - Dang, J K; Thakur, D P; Singh, R K; Singh, F (Annals of Arid Zone, 2016)
Inheritance studies of downy mildew of pearl millet was done under epiphytotic condition, in the Fl and F2 population of a full diallel crosses involving 10 parents. Genotypic differences were highly significant in both the generations. Combining ability analysis showed highly significant mean squares due to general combining ability (GCA) and specific combining ability (SCA) in both the generations. Significant mean square due to reciprocals were also significant. The parents 15!8, 1548 and 76-32-1 were found resistant and also had negative significant GCA effects. The crosses involving these parents were also resistant. All the three analyses i.e. graphical, component and combining ability indicated that the character is controlled by both additive dominant gene effects. The resistance was found to be partially dominant over susceptibility. Graphical analysis showed that resistant parents mainly had dominant genes. Heritability estimates were high in both the generations.